Strategi Komunikasi Pemasaran Terpadu melalui Media Sosial Instagram "Nona Judes" - Bintang Nurijadi; Novida Irawan; Fransiska Fransiska; Ambarwati Ambarwati (MUKASI: Jurnal Ilmu Komunikasi, 2024)
The development of technology and communication has experienced quite amazing developments and made it easier for someone to promote products for sale, especially food and beverage products. Promotion is very important in marketing a product offline or online. Before online, offline influenced selling a product to the communicant, face to face, being able to see the expression on the communicant's face directly, as technology develops now, online sales increasingly influence sales because the sophistication of current technology greatly influences marketing developments. This research aims to determine the Integrated Marketing Communication Strategy via Instagram Social Media "Miss Judes". The theory used in this research is Integrated Marketing Communication. The method used in this research is descriptive qualitative. The data collection technique is conducting in-depth interviews, where the interview is intended to obtain data and information that is reliable and can be accounted for. So the researcher conducted interviews with key informants and informants. Data analysis techniques are collected, analyzed, and interpreted to obtain an overview of the observed variables, through data reduction. The research results show that Miss Judes' marketing communication strategy carries out product and service promotion activities through Instagram social media. Through social media, these activities are more effective, whereas Instagram social media only relies on internet quota or WiFi, which is different from direct promotion.